1993
DOI: 10.1103/physrevb.48.7099
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the perpendicular magnetoresistance in magnetic multilayers

Abstract: By starting with the Boltzmann equation, we calculate the transport properties of magnetic multilayers for currents perpendicular to the layers. Our model takes into account both volume and interface spin-dependent scattering. We show that the macroscopic equations already used by Johnson et al. or van Son et al. are justified if the spin-diffusion length is much longer than the mean free path, even for individual layer thicknesses of the order of the mean free path. But, second, we show that Johnson's assump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
1,405
3
13

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,676 publications
(1,465 citation statements)
references
References 21 publications
33
1,405
3
13
Order By: Relevance
“…As shown in Figure 2c, the dependences of the spin signal on the interval L for both devices were well fitted using the one-dimensional spin diffusion equation with transparent interfaces, which is given by [23][24][25] …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2c, the dependences of the spin signal on the interval L for both devices were well fitted using the one-dimensional spin diffusion equation with transparent interfaces, which is given by [23][24][25] …”
Section: Resultsmentioning
confidence: 99%
“…However, in the left lead, we expect μ L = μ L↑ − μ L↓ = 2μ L Q to be proportional to I spin . 40 Therefore, the function Q(V ) is highly nonlinear and needs a priori to be determined self-consistently. However, this turns out to be a very difficult task (this is a nonlinear and nonequilibrium interacting problem).…”
Section: Kondo Resonance In the Presence Of A Bias-dependent Spinmentioning
confidence: 99%
“…38 As demonstrated by Johnson 39 (see also Refs. [40][41][42], a spin current induces spin accumulation yielding spin-dependent chemical potentials μ ↑ = μ ↓ , which is equivalent to a spin bias. Using the equation of motion approach, Qi et al analyzed the fate of a Kondo resonance in the presence of spin accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The demand of higher areal density exceeding 2 Tbit/in 2 in hard disc drives (HDDs) highlights current-perpendicularplane (CPP)-GMR devices as a potential successor of the present tunneling magnetoresistive (TMR) device for next generation read head sensors due to its intrinsically low resistance area product (RA) for higher frequency responses. [4][5][6][7] Recently, substantial large MR ratios at room temperature (RT) were realized in fully epitaxial CPP-GMR devices with the usage of the Co-based Heusler alloys such as Co 2 MnSi (CMS), 8 Co 2 Mn(Ga 0.25 Ge 0.75 ) (CMGG), 9 Co 2 (Fe 0.4 Mn 0.6 )Si (CFMS), 10 and Co 2 Fe(Ga 0.5 Ge 0.5 ) (CFGG). 11 Such a high MR output in a low resistance device has already satisfied the MR performance required for the areal density of 2 Tbit/in 2 according to the simulation by Takagishi et al 7 However, all of these high MR outputs have only been demonstrated for the epitaxial CPP-GMR pseudospin-valves (PSVs) grown on unpractical MgO single crystalline substrates, which are too expensive for mass production and incompatible with the current semiconductor industry processes.…”
mentioning
confidence: 99%